Processo de secagem da goma de cajueiro (Anacardium occidentale L.) e suas propriedades tecnológicas - Souza, Valéria Melo de (2011)
Tropical countries such as Brazil, are deposits of a variety of sources of plant polysaccharides known and others not yet explored that have great potential in industrial applications. The cashew tree gum may be cited as one of these polysaccharides. Some studies report the possibility of using cashew gum in various sectors and for their structural similarity to the gum arabic, has been suggested as a replacement. Therefore, this project proposes to increase the existing knowledge on the technological properties of cashew gum and evaluate the real potential replacement of gum arabic To do so, will perform the different drying methods after purifying the gum, and physical-chemical, rheological and technological. The release of industrial use of cashew gum would be a breakthrough, especially for the food industry, where the material would find numerous applications, replacing (with economic advantages) gum arabic, and can be used in applications for which gum arabic is not used for economic reasons. Eventually, the industrial production of cashew gum could give Brazil independence from imports of gum arabic, and also enter a highly competitive product in its exports This work aimed to study different methods of drying of cashew gum (Anarcadium occidentale L), evaluating their technological properties. It was observed that some characteristics of cashew gum the moisture, ash, water activity and pH were determined for the starch in the various drying methods. The levels of minerals (Na, Ca, K, Mg) present in the gum were analyzed using the method of X-ray The protein content, but did not decrease significantly during drying, which may indicate that it is aggregated to the polysaccharide. The level of solubility, hygroscopicity, viscosity, water absorption capacity and oil was determined over all drying methods.